Post-transplant Diabetes Mellitus in Kidney Transplant Recipients: A Multicenter Study. Issue 8 (26th August 2021) - Malik, Rubab F.; Jia, Yaqi; Mansour, Sherry G.; Reese, Peter P.; Hall, Isaac E.; Alasfar, Sami; Doshi, Mona D.; Akalin, Enver; Bromberg, Jonathan S.; Harhay, Meera N.; Mohan, Sumit; Muthukumar, Thangamani; et al.
Visual Abstract: Abstract: Key Points: Post-transplant diabetes mellitus (PTDM) occurred commonly in a multicenter longitudinal cohort of 632 kidney transplant recipients. Independent risk factors for PTDM included older recipient age and higher body mass index at time of transplant. PTDM was not associated with adverse graft outcomes or mortality at a median follow-up of 6 years after transplant. Background: De novo post-transplant diabetes mellitus (PTDM) is a common complication after kidney transplant (KT). Most recent studies are single center with various approaches to outcome ascertainment. Methods: In a multicenter longitudinal cohort of 632 nondiabetic adult kidney recipients transplanted in 2010–2013, we ascertained outcomes through detailed chart review at 13 centers. We hypothesized that donor characteristics, such as sex, HCV infection, and kidney donor profile index (KDPI), and recipient characteristics, such as age, race, BMI, and increased HLA mismatches, would affect the development of PTDM among KT recipients. We defined PTDM as hemoglobin A1c ≥6.5%, pharmacological treatment for diabetes, or documentation of diabetes in electronic medical records. We assessed PTDM risk factors and evaluated for an independent time-updated association between PTDM and graft failure using regression. Results: Mean recipient age was 52±14 years, 59% were male, 49% were Black. Cumulative PTDM incidence 5 years post-KT was 29% (186). Independent baseline PTDM risk factors included older recipient age ( P <0.001) and higher BMI ( P =0.006). PTDM was not associated with all-cause graft failure (adjusted hazard ratio (aHR), 1.10; 95% CI, 0.78 to 1.55), death-censored graft failure (aHR, 0.85; 95% CI, 0.53 to 1.37), or death (aHR, 1.31; 95% CI, 0.84 to 2.05) at median follow-up of 6 (interquartile range, 4.0–6.9) years post-KT. Induction and maintenance immunosuppression were not different between patients who did and did not develop PTDM. Conclusions: PTDM occurred commonly, and higher baseline BMI was associated with PTDM. PTDM was not associated with graft failure or mortality during the 6-year follow-up, perhaps due to the short follow-up time.